Metformin - An Antidiabetic Drug With Anti-aging, Cardioprotective And Potential Anti-cancer Properties - Jabłonowska, Magdalena; Grzeszczuk, Paulina; Kaczmarek, Aleksandra; Kaczmarek, Wojciech; Krakowiak, Magdalena (Journal of Education, Health and Sport, 2025)
Introduction: This review aims to examine the role of metformin, a widely used oral antihyperglycemic agent, and its emerging potential cardioprotective, anticancer, and anti-aging effects. Materials and Methods: A comprehensive review of the literature was conducted using the PubMed and Google Scholar databases using the following keywords: “metformin”, “anti-aging”, “cardioprotective”, ”anti-cancer”, “AMPK”, “diabetes”, “anti-inflammatory”, “cancer”, “mTOR” Summary: Metformin, originally developed to treat type 2 diabetes, has been widely used due to its effectiveness in lowering blood glucose without causing hypoglycemia, and it exhibits a strong safety profile with additional benefits like weight loss and improved cardiovascular health. Beyond diabetes management, metformin shows promising anti-aging effects by improving mitochondrial function, regulating protein homeostasis, reducing inflammation, and modulating the microbiome. Furthermore, metformin has potential protective roles against dementia, skin aging, cardiovascular diseases, and various cancers through mechanisms involving AMPK activation and immune modulation. Conclusions: Metformin demonstrates a wide range of beneficial effects beyond glucose control, including anti-aging, anti-inflammatory, cardiovascular protective, and potential anticancer properties. Through its cellular and metabolic mechanisms, metformin shows promise not only as a treatment for type 2 diabetes but also in the prevention and management of various age-related diseases. However, more high-quality clinical studies are needed to confirm these findings.